HUBUNGAN HASIL BELAJAR MICRO TEACHING DENGAN HASIL BELAJAR PROGRAM PENGALAMAN LAPANGAN (PPL) MAHASISWA JURUSAN TADRIS/PENDIDIKAN MATEMATIKA PADA ANGKATAN 2013 IAIN PADANGSIDIMPUAN - Siregar, Rahma Hayati (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
This study aims to find out (1) the result of learning micra teaching students majoring in tadris/mathematics education in the class of 2013 IAIN Padangsidimpuan, (2) the result of learning program field experience students majoring in tadris/mathematics education in 2013 IAIN Padangsidimpuan, (3) micro teaching students with learning outcomes of field experience program students majoring in tadris / mathematics education in forse 2013 IAIN Padangsidimpuan. Data were collected by documentation and analyzed by Product Moment Correlation. The result showed that (1) the lowest learning achievement of micra teaching was 68, the highest learning result was 90, the average score was 79.63, (2) the lowest learning achievement of the experiential learning achievement (PPL) 81, the highest learning result 94, average score 87.33, (3) there is a positive correlation between result of learning of micro teaching with result of learning program field experience of students majoring tadris/mathematics education at class of 2013 IAIN Padangsidimpuan done t test. Based on calculations obtained t_hit = 0.3408 and t_table = 0.329 with n = 36 and Î± = 0.05. Based on the analysis result obtained that t_hit t_table, meaning there is a significant relationship between the results of learning micro teaching with the result of learning programs field experience students majoring in Tadris / Mathematucs education in the class 2013 IAIN Padangsidimpuan.